Prevalencia de eventos trombóticos en pacientes con enfermedad inflamatoria intestinal conseguimiento en un centro de referencia de la Ciudad de Buenos Aires: estudio de corte transversal - Perez, Tomas Manuel (2022)
Introduction. Inflammatory bowel diseases are systemic disorders that affect the gastrointestinal tract and may present multiple extraintestinal manifestations. Among them, thromboembolic disease stands out and has a great impact on the morbidity and mortality of these patients. The risk of thrombosis in patients with inflammatory bowel disease is almost twice that of the general population, as reported in the literature. Risk factors described for this association include: inflammatory disease activity, hospitalization, recent surgeries, disease extension, and treatments of these conditions. Aim. The main objective of this study was to determine the prevalence of thrombotic events in the population of patients with inflammatory bowel disease followed in a third-level hospital in the city of Buenos Aires and, secondarily, to evaluate the rate of thrombosis in hospitalized patients and in the outpatient population, as well as the associated clinical characteristics. Materials and methods. A descriptive cross-sectional study was conducted that included patients with a diagnosis of inflammatory bowel diseases (Crohn's disease and ulcerative colitis) with follow-up in our center, who developed thrombotic events in the period from January 2002 to December 2020. The electronic medical record was used as a tool to detect and analyze the population of patients diagnosed with inflammatory bowel disease and who suffered the event of interest. Results. A total of 1,753 patients with inflammatory bowel disease were included: 1,352 with ulcerative colitis and 401 with Crohn's disease. Thirty-six of these patients developed the event of interest, resulting in a prevalence of thrombosis in patients with inflammatory bowel diseases of 2.0% (95% CI:1.0-2.8%). Within this group, 77.7% (28) of the events occurred in the outpatient setting and 22.2% (8) in patients. Of the patients with thrombosis, 39.2% (11) had a history of recent hospitalization (in the previous 60 days) and, of this group, 54% (6) developed thrombosis within the first month of discharge. Conclusions. The prevalence of thrombosis, in our population with this condition, was 2%. Most thrombotic events occurred in the outpatient setting. This raises the need for further studies to determine the behavior of instituting prophylactic measures in this group, especially in patients who have required recent hospitalization.